2011
DOI: 10.1139/y11-065
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sensitization involved in dexmedetomidine-induced contraction of isolated rat aorta

Abstract: Dexmedetomidine, a full agonist of the α2B-adrenoceptor that is mainly involved in vascular smooth muscle contraction, is primarily used for analgesia and sedation in intensive care units. High-dose dexmedetomidine produces hypertension in children and adults. The goal of this in vitro study was to investigate the role of the calcium (Ca(2+)) sensitization mechanism involving Rho-kinase, protein kinase C (PKC), and phosphoinositide 3-kinase (PI3-K) in mediating contraction of isolated rat aortic smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 34 publications
14
20
0
Order By: Relevance
“…In agreement with previous reports, rauwolscine attenuated dexmedetomidine-induced contraction, suggesting that dexmedetomidine-induced contraction involves activation of the α-2 adrenoceptor [15,21,22,23]. Similar to previous reports, chelerythrine and Y-27632 attenuated dexmedetomidine-induced contraction in a concentration-dependent manner, suggesting that dexmedetomidine-induced contraction is mediated by PKC and Rho-kinase [15,21,23,24].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with previous reports, rauwolscine attenuated dexmedetomidine-induced contraction, suggesting that dexmedetomidine-induced contraction involves activation of the α-2 adrenoceptor [15,21,22,23]. Similar to previous reports, chelerythrine and Y-27632 attenuated dexmedetomidine-induced contraction in a concentration-dependent manner, suggesting that dexmedetomidine-induced contraction is mediated by PKC and Rho-kinase [15,21,23,24].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous reports, chelerythrine and Y-27632 attenuated dexmedetomidine-induced contraction in a concentration-dependent manner, suggesting that dexmedetomidine-induced contraction is mediated by PKC and Rho-kinase [15,21,23,24]. Consistent with a previous report, ML-7 hydrochloride attenuated dexmedetomidine-induced contraction, suggesting that dexmedetomidine-induced contraction involves activation of myosin light chain kinase [24].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interactions of α 2 -ARs with PKC have been suggested to lead to Ca 2+ influx and vasoconstriction [14,17]. Kim et al recently reported that activation of α 2 -ARs by dexmedetomidine resulted in a constriction response involving a Ca 2+ sensitization mechanism mediated by Rho kinase, PKC, and phosphatidylinositol 3-kinase [26]. …”
Section: Discussionmentioning
confidence: 99%